Determinant Factors of Customer Satisfaction Degree of China Mobile in Beijing, China - Sun, Shuai (2016)
Telecommunication services in China are mainly provided by China telecom corporations, China Unicom, and China Mobile. China’s telecommunications industry began in November of 1987 and only had more than 150 subscribers during that time. According to Verto and iResearch data, there is 48% of the online population in China currently from the total global population which approximately 651, 360, 000 people at the time of writing. In contrast, while there is 85% of Americans are online compare to China has almost 2.5X the online community. However, the devices people in China are using to access the Internet might surprise you. The simultaneous trend of China-focused services such as Baidu and Alibaba had gaining momentum from the last five years which had overlapped along with the emergence of smartphones and increasingly affordable mobile devices. In fact, this growth can be seen in headline-grabbing Chinese apps such as WeChat CINIC believes that only 186 million rural Chinese currently access the web, something that has massive implications for growth given advances in mobile technology. Therefore there is an urgent need for the service provider to improve their customer satisfaction for the sake of customer retention and develop more perspective customers.